Design and Development of a Multimedia-Based Promotional Website for Digital Branding at LKP KARYA PRIMA KURSUS Using the Waterfall Method - Supiyandi Supiyandi; Eka Pandu Cynthia; Wizra Aulia; Husni Mubarak; Chairul Rizal (Jurnal Komputer Teknologi Informasi Sistem Komputer (JUKTISI), 2026)
Digital transformation in the education sector requires educational institutions to provide promotional media that deliver information quickly, interactively, and efficiently. LKP KARYA PRIMA KURSUS continues to experience limitations in information dissemination due to the reliance on conventional promotional approaches, reducing the effectiveness of digital branding and communication with prospective students. A multimedia website was developed to provide an integrated promotional platform that increases institutional visibility, accelerates access to information, and supports digital registration services. The Waterfall methodology was applied through the stages of requirements analysis, system design, implementation, testing, and maintenance. The implementation results demonstrate that the website was successfully developed with a responsive architecture that effectively presents multimedia content across desktop and mobile devices. System testing confirmed that all primary features operated according to functional specifications without critical errors. The integration of interactive multimedia improved the quality of information delivery and strengthened the institution’s digital brand identity. In addition, server optimization and responsive interface design produced stable page accessibility and efficient performance under various network conditions. The developed system also supports scalability for future feature expansion, including interactive services and real-time communication modules. These findings indicate that applying the Waterfall method effectively produces a multimedia promotional website that supports institutional promotion and digital branding in the educational sector.